Sorghum and millet as alternative grains in nutrition - Jevcsák, Szintia; Sipos, Péter (Acta Agraria Debreceniensis, 2016)
Sorghum (Sorghum bicolor L.) and millet (Panicum miliaceum L.) are the fifth and sixth most important cereal crops in the world. Gluten-free grains, therefore persons with coeliac disease could consume them also. In addition, they have a lot of positive effects due to their phenolic compounds (phenol acid, flavonoid, tannin). The total phenol content of sorghum is high, but Panicum miliaceum and Eleusine coracana have higher antioxidant activity. Fiber and mineral contents are also high, the protein contents are also higher than in standard cereals. Sorghum use is similar to corn: starch, glucose, syrup, and oil can be produced. Moreover, it can be used in preparing whole grain products, bread, pancake, dumpling, mush, cake, pasta and beer from sorghum. Broom and forage are also can be prepeared from them. Millet used such as mush, steamed food, cake, bread, alcoholic and non-alcoholic beverages.